The cost of care in maxillofacial fractures treatment in relation to the type of fixation and length of stay at a tertiary care hospital of Karachi, Pakistan: a retrospective chart review - Humayun Kaleem Siddiqui; Ghauri, Kanza; Khan, Farhan Raza (Journal of the Pakistan Medical Association, 2024)
In addition to the clinical burden of trauma, the financial burden is an important aspect of care globally, especially for patients in low- and middle-income countries. The current retrospective review was done of data from January 2015 to December 2020 related to patients of oral maxillofacial trauma management in a tertiary care setting. Analysis of variance was used to determine the mean difference in the cost incurred depending upon the type of trauma and the number of bone plates used in fracture management. Pearson correlation was applied to explore any correlation involving patient age, aetiology and type of fracture, number of bone plates employed and the length of stay in the hospital. No statistically significant differences were noted in the cost among the different groups. —Continue